Prevention of Secondary Victimization for Victims of Sexual Violence in Court Proceeding - Dinah Faizah Syahbur; Aroma Elmina Martha; Galuh Praharafi Rizqia (Contemporary Issues in Criminal Law, 2024)
The number of sexual violence cases against women remains a concern faced by Indonesian society. Ideally, when a sexual violence occurs, the victim shall report the crime. However, while undergoing the process to demand justice, it is not uncommon for victims of sexual violence to experience the secondary victimization wherein the victim is blamed for the crime instead and receives negative stigma from the law enforcement officials. This study focuses on the causal factors for the occurrence of secondary victimization for victims of sexual violence in the court proceeding and strategies to prevent such phenomenon. This study is a combined empirical and doctrinal legal research focusing on the interview with the officials of legal institution and judges concerning this issue supported by existing regulations. It is argued that many law enforcement officials are still lacking the perspective of the victim and having no understanding on the dynamics of the victims in the aftermath of the crime. Various prevention of secondary victimization has been provided, such as the existence of legal assistance by Rifka Annisa psychological centre as well as the relevant Supreme Court Regulation. During examination in court, judges should prevent and/or reprimand parties, legal counsel, public prosecutors, and/or attorneys who behave or make statements in ways that demean, blame, intimidate and/or use the experience or sexual background of women in conflict with the law. Law Number 12 of 2022 can be implemented immediately so that law enforcement officials can prioritize the interests of victims and implement related procedures for handling victims of sexual violence in the criminal justice system. Keywords: Secondary victimization, Sexual violence, Court hearing process Abstrak Banyaknya kasus kekerasan seksual terhadap perempuan masih menjadi perhatian yang dihadapi masyarakat Indonesia. Ketika kekerasan seksual terjadi, korban harus melaporkan kejahatan tersebut. Namun, saat menjalani proses menuntut keadilan, tidak jarang korban kekerasan seksual mengalami viktimisasi sekunder dimana korban malah disalahkan atas kejahatan tersebut dan menerima stigma negatif dari aparat penegak hukum. Penelitian ini berfokus pada faktor-faktor kasual terjadinya viktimisasi sekunder bagi korban kekerasan seksual dalam sidang pengadilan dan strategi untuk mencegah fenomena ini. Penelitian ini merupakan gabungan penelitian hukum empiris dan doktrinal yang berfokus pada wawancara dengan pejabat lembaga hukum dan hakim mengenai masalah ini yang didukung oleh peraturan yang ada. Dikatakan bahwa banyak aparat penegak hukum masih kurang perspektif korban dan tidak memahami dinamika korban pasca kejahatan. Berbagai pencegahan viktimisasi sekunder telah diberikan, seperti adanya pendampingan hukum oleh Rifka Annisa dan Peraturan Mahkamah Agung. Selama pemeriksaan di pengadilan, hakim harus mencegah dan/atau menegur pihak, penasihat hukum, penuntut umum, dan/atau pengacara yang berperilaku atau membuat pernyataan yang merendahkan, menyalahkan, mengintimidasi dan/atau menggunakan pengalaman atau latar belakang seksual perempuan yang berkonflik dengan hukum. Peraturan nomor 12 tahun 2022 ini dapat segera diimplementasikan agar aparat penegak hukum dapat mengutamakan kepentingan korban dan melaksanakan prosedur terkait penanganan korban kekerasan seksual dalam sistem peradilan pidana. Kata kunci: Viktimisasi sekunder, Kekerasan seksual, Proses sidang pengadilan